A longitudinal, multi-level comparative study of quality and safety in European hospitals: the QUASER study protocol. - Robert, G; Anderson, J; Burnett, S; Aase, K; Andersson-Gare, B; Bal, R; Calltorp, J; Nunes, F; Weggelaar, A; Vincent, C; Fulop, N (BioMed Central, 2011)
BACKGROUND: although there is a wealth of information available about quality improvement tools and techniques in healthcare there is little understanding about overcoming the challenges of day-to-day implementation in complex organisations like hospitals. The 'Quality and Safety in Europe by Research' (QUASER) study will investigate how hospitals implement, spread and sustain quality improvement, including the difficulties they face and how they overcome them. The overall aim of the study is to explore relationships between the organisational and cultural characteristics of hospitals and how these impact on the quality of health care; the findings will be designed to help policy makers, payers and hospital managers understand the factors and processes that enable hospitals in Europe to achieve-and sustain-high quality services for their patients. METHODS/DESIGN: in-depth multi-level (macro, meso and micro-system) analysis of healthcare quality policies and practices in 5 European countries, including longitudinal case studies in a purposive sample of 10 hospitals. The project design has three major features: • a working definition of quality comprising three components: clinical effectiveness, patient safety and patient experience • a conceptualisation of quality as a human, social, technical and organisational accomplishment • an emphasis on translational research that is evidence-based and seeks to provide strategic and practical guidance for hospital practitioners and health care policy makers in the European Union. Throughout the study we will adopt a mixed methods approach, including qualitative (in-depth, narrative-based, ethnographic case studies using interviews, and direct non-participant observation of organisational processes) and quantitative research (secondary analysis of safety and quality data, for example: adverse incident reporting; patient complaints and claims). DISCUSSION: the protocol is based on the premise that future research, policy and practice need to address the sociology of improvement in equal measure to the science and technique of improvement, or at least expand the discipline of improvement to include these critical organisational and cultural processes. We define the 'organisational and cultural characteristics associated with better quality of care' in a broad sense that encompasses all the features of a hospital that might be hypothesised to impact upon clinical effectiveness, patient safety and/or patient experience.